Influence of Extract Swiftlet Nest (Collocalia Fuciphago) as Antihyperglycemia to Circulating Endothelial Cells in Rat (Rattus novergicus) Induced by Streptozotocin - Francisca Diana Alexandra; Satriyandi M; Agnes Frethernety; Triawanti Triawanti (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: Hyperglycemia could increase the oxidative stress by catalyzes the formation of free radical as anion superoxide(O2-). Oxidative stress will effect in endothelial damaged. This study aimed to evaluated the influence of extract swiftlet nest (Collocalia fuciphago) to glucose level and CEC in rat (Rattus novergicus). Rats were classified into 4 groups, there were control group (K) and 3 treatments group (dose 1; 10 and 100 mg / kgBW) The seventh day after induced by Streptozotozin (i.p), the rats had increased glucose ± 102 – 108 mg/dL, then treated with the extract of Swiftlet nest for 28 days by oral. The CEC was measured by Hladovec method. The results showed the blood glucose level were significant differences ( p = 0.035). The number of CEC decrease significantly (p=0,002). In conclusion that extract of Swiftlet nest can effect to decrease glucose level and CEC number in plasma rat (Rattus novergicus) Keywords: Hyperglycemia, Circulating Endothelial Cells, Collocalia fuciphago